Intelligenza Artificiale: con il Medioevo nel cuore - Caligiuri, Mario (Studi sulla Formazione/Open Journal of Education, 2024)
The paper analyzes the evolution of universities in the age of artificial intelligence, highlighting the challenges and opportunities arising from rapid technological transformation. Through a journey that starts from the medieval roots of universities, it explores the interaction between human and artificial intelligence, the reshaping of traditional knowledge monopolies, and the emergence of new learning and teaching methods. The reflections emphasize the critical role of ethics, intelligence, and beauty in addressing global changes, underlining the importance of an integrated approach between technological innovation and human values. Finally, it focuses on the educational crisis and potential solutions to make universities a pillar in building a sustainable and inclusive future.